Characterizing historical (1992–2010) transitions between grassland and cropland in mainland France through mining land-cover survey data - Ying Xiao; Catherine Mignolet; Jean-François Mari; Marc Benoît (Journal of Integrative Agriculture)
Grassland, as one of the largest ecosystems on the earth, supports various goods and services to humanity. Historically, humans have increased agricultural output primarily by cropland expansion and agricultural intensification. The cropland area was primarily gained at the expense of grassland and forests. Apart from grassland conversion, increasing consumption of calorie- and meat-intensive diets drives the intensification of livestock systems, which is shifting steadily from grazing to feeding with crops. To cope with the environmental degradation due to agriculture, various forms of ‘green payment’ were implemented to promote the adoption of sustainable farming practices over the last two decades in the European Union. The aim of this study is to monitor the recent transitions (1992–2010) between grassland and cropland during two Common Agricultural Policy (CAP) reforms at the French mainland scale. We proposed an innovative approach to link grassland conversion to agricultural commodities and farming systems practices. We first assessed the grassland-to-cropland conversion and further investigated the crop sequence patterns that were observed to be dominant after the conversion through mining land-cover survey data Teruti and Teruti-Lucas. We found the trends of the transitions between grassland and cropland over the two time intervals: The loss of grassland (1992–2003) and restoration or re-expansion of grassland (2006–2010) in mainland France. Our finding on the crop sequence patterns after the grassland conversion reveals two notable evolutions of agricultural production systems. These evolutions were related to the increase in the proportion of cropland in the total agricultural land use. One evolution was most likely influenced by the demand for fodder: The conversion from grazing livestock to feeding livestock. Another evolution was the conversion from livestock production to field crop production. Our results indicate that the intensification of livestock farming systems continued over the last two decades in France. We conclude that, the approach developed in this study can be considered as a generic method for monitoring the transitions between grassland and cropland and further identifying the crop sequence patterns after the grassland conversion from time-series land cover data.